Analisis Pengaruh Lingkungan Ekternal terhadap Penjualan Tenaga Listrik di PT PLN (Persero) UIN Sumatera Utara - Bima Prakasa; Sukaria Sinulingga; Syafrizal Situmorang (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
All countries in the world are experiencing a wave of business, industrial and technological revolutions that contribute greatly to the improvement of a country's economy. This development brings golden opportunities for electricity companies to increase their sales. The demand for electricity will continue to increase along with the development of technology, business, and industry. Sales channels are strongly influenced by external factors in the form of political, economic, social, technological, legal, and ecological factors. This research is associative research. In this study there are independent variables and dependent variables. The research focuses on the influence of the external environment, namely political, economic, social, technological, legal, and ecological factors as independent variables on electricity sales as the dependent variable. The data collection method used in this research by distributing questionnaires to customers. From the research that has been done, it is known that political factors, economic factors, social factors, technological factors, and ecological factors have a positive and significant effect on electricity sales. The external environment simultaneously has a positive effect on the sales of electricity. Seeing the magnitude of the influence of the external environment on electricity sales, it is only natural that management is aware of any external issues that may occur that can affect business performance. The author recommends that management create a team tasked with overseeing stakeholder management related to this issue, so that action can be taken when rapid changes occur in the external environment.